2010
DOI: 10.1007/s00540-010-0970-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular levobupivacaine or bupivacaine administration decreases pain scores and provides a better recovery after total knee arthroplasty

Abstract: Intraarticular bupivacaine and levobupivacaine provided better postoperative analgesia both at rest and during mobilization in total knee replacement surgery compared to control. Tramadol consumption and hospital stay were also decreased in the study groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…According to the results of our study the VAS scores were found to be lower in the bupivacaine group in the initial few hours postoperatively (4,8,12,24 hours), but they were lower for the levobupivacaine group at the 48 th hour, virtually everything else such as the requirement for PCEA (boluses and dosage), physiotherapy associated pain, discharge and mobilization times were identical. We had utilized in our study intra articular injections of the two drugs, paracetamol and PCEA as modalities to relieve the postoperative pain.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…According to the results of our study the VAS scores were found to be lower in the bupivacaine group in the initial few hours postoperatively (4,8,12,24 hours), but they were lower for the levobupivacaine group at the 48 th hour, virtually everything else such as the requirement for PCEA (boluses and dosage), physiotherapy associated pain, discharge and mobilization times were identical. We had utilized in our study intra articular injections of the two drugs, paracetamol and PCEA as modalities to relieve the postoperative pain.…”
Section: Discussionmentioning
confidence: 50%
“…All the patients were monitored intra operatively using standardized equipment. Readings of echocardiograph, blood pressure and pulse oximetry at regular time intervals (at 5,15,30,60 and 90 mins or till end of procedure) as well as sensory and motor characteristics of the established block at various intervals (2,4,8,12,24,48 and 72 hours postoperatively) side effects, number of boluses and doses of PCEA, total amount of pain relief medications utilized over the period was observed, VAS scores and time of mobilization and discharge from the hospital were also noted in a pre-designed proforma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Kazak Bengisun et al found that use of levobupivacaine and bupivacaine intra-articularly produced lesser rescue analgesic consumption and lower VAS score which was similar to our study. [12] Paul et al concluded that intra-articular dexmedetomidine added as an adjunct to ropivacaine in patients undergoing arthroscopic knee surgery improved the quality and duration of postoperative analgesia. [13] Das et al in their study compared intraarticular ropivacaine ,fentanyl and dexmedetomidine for pain relief and suggested that ropivacaine was better than both fentanyl and dexmedetomidine.…”
Section: Resultsmentioning
confidence: 99%
“…We are fully aware of and share Dr Zink's concerns about the chondrotoxic effects of local anesthetics. Dr Zink pointed out that "there is good evidence that intra-articular injection of local anesthetics may result in severe damage in cartilage tissue"; however, as far as we know there are no data about the chondrotoxic effect of levobupivacaine while anesthesiologists are using it widely in the clinic even intra-articularly [1,2]. For these reasons we designed this study.…”
mentioning
confidence: 99%